Survey and explain the role of sensemaking in successful strategy implementation in Iran’s automotive companies - Khodadad Hosseini, Seyed Hamind; Hosseini, Seyed Farhad; Kordaniej, Asadollah; Ahmadi, Parviz (Business: Theory and Practice, 2016)
There is not a dominant model that could explain key factors of sensemaking of strategy implementation and interactions between them. The purpose of this study is designing and explaining the role of sensemaking in successful strategy implementation along with a combination of factors which inﬂuence implementation sensemaking. This study surveyed the factors inﬂuencing sensemaking of successful strategy implementation in top Iran’s automotive companies. This is a qualitative research that uses grounded theory to obtain insight about the role of sensemaking in successful implementation through in-depth interviews with 22 individuals (Managers, Assistant Directors and Academic Professors) and used gathered data to design a model of sensemaking in successful strategy implementation. Based on open and axial coding, 21 effective variables were conceptualized and classified in seven major categories then final model was designed. This theory explains factors that affect the sensemaking of successful strategy implementation and how these factors interact with each other. Sensemaking in Successful implementation of strategies depends on Sensemaking Context, Key Executers, Discourse Context, Intervening Conditions and Collective Sensemaking. Sensemaking Context cause sensemaking and sensegiving of key executers and key executers itself along with Discourse Context and Intervening Conditions lead to collective sensemaking. The consequence of model is sensemaking of successful strategy implementation that consists of maintaining and recording the meaning and its strengthening, collective effort, continuous strategy implementation and operational excellence of the organization.